The Influence Of Live Streaming, Discounts, And Content Marketing On Purchasing Decisions On Tiktok Shop (Study On Generation Z Consumers in Sidoarjo) - Putri, Cindy Ananda; Muhammad Yani; Mas Oetarjo (University of Darussalam Gontor, 2024)
Tiktok is a creative video application developed by the Chinese-based company Bytedance, China in September 2016. Tiktok's popularity began to skyrocket in 2018. It has been downloaded 67.4 million times in Indonesia in 2023. In September 2021, Tiktok adapted by adding a shopping feature to its application known as Tiktok Shop. This study aims to measure the level of influence of live streaming, discounts, and content marketing on purchasing decisions at Tiktok Shop. The sampling technique in this study used a purposive sampling technique and used the Lemeshow formula to determine the number of samples due to the unknown population, with a result of 100 respondents. Data collection was carried out by distributing questionnaires to Tiktok Shop users. This study is quantitative and uses the SmartPLS analysis tool. The results of the study show that live streaming, discounts, and content marketing have a positive and significant effect on purchasing decisions at Tiktok Shop in Sidoarjo.